KEMERDEKAAN PERS, SEBUAH PONDASI HAK ASASI MANUSIA DITINJAU DARI UU NO. 40 TAHUN 1999 - Ramon Kaban (Perspektif, 2004)
Press freedom is implementation of people sovereignty and democratic country In a law based democratic country such as Indonesia, human rights must be consistently implemented especially in absolute rights, i.c. civil and politics rights. Politics rights in the context of human rights include freedom to give opinion, written and oral, which will be the basic of press freedom that has been regulated in UU no. 40, 1999.